Conjugated linoleic acid in adipose tissue and risk of myocardial infarction - Smit, Liesbeth A. (2010)
Despite the high saturated fat content of dairy products, no clear association between dairy product intake and risk of myocardial infarction (MI) has been observed. Dairy products are the main source of conjugated linoleic acid (CLA; 18:2n27t), which is produced by the ruminal biohydrogenation of grasses eaten by cows. Pasture-grazing dairy cows have more CLA in their milk than do grain-fed cows. Some animal models have reported beneficial effects of CLA on atherosclerosis.